Validasi Berat Ikan Pada Produk Olahan Ikan Dalam Kemasan Kaleng Di Surakarta - Setyaningrum Rahmawaty; Dita Ayu Setyaningtyas (Bioeksperimen: Jurnal Penelitian Biologi, 2021)
Fish is the main dietary source of omega-3 long chain polyunsaturated fatty acids (n-3 LCPUFA) including eicosapentaenoic acid (EPA), docosapentaenoic acids (DPA) and docosahexaenoic acid (DHA) which have benefits to maintain an optimal health. The purpose of this study was to validate fish content in canned fish products in order to develop fish database for dietary assessment. A market survey was performed in 10 supermarkets which were randomly selected in Surakarta followed by laboratory analysis to measure fish content based on CODEX standard for canned fish. The study was conducted in July until November 2019. Results showed that there were 32 serving size from 11 branches of canned fish with the majority fish type was sardine (n=24) followed by mackerel (n=5) and tuna (n=3). They served in various taste such as in tomato sauce, chili sauce, brine and vegetable oil. The percentage of fish content in the labels was in a range from 50% to 70%. There was no significance difference between the percentage of fish mentioned in the canned fish labels and based on measurement in laboratory (Independent Sample T-test dan Mann-Whitney U test, p0.05). Given the variation of fish content in the canned fish products, it is recommended to consider the percentage of fish in estimating individual fish intake.